Boosting Microglial Lipid Metabolism via TREM2 Signaling by Biomimetic Nanoparticles to Attenuate the Sevoflurane‐Induced Developmental Neurotoxicity - Wenting Li; Xiaowen Meng; Ke Peng; Yaobao Han; Hanghang Liu; Weiming Zhao; Gang Wang; Li Deng; Hong Liu; Zhen Li; Fuhai Ji (Advanced Science, 2024)
Abstract Lipid metabolism has been considered as a potential therapeutic target in sevoflurane‐induced neurotoxicity that can potentially affect the learning and memory function in the developmental brain. Recently, triggering receptor expressed on myeloid cells 2 (TREM2) is identified as a crucial step in regulating lipid metabolism and associated with the pathogenesis of neurodegenerative diseases. Herein, it is reported that quercetin modified Cu2‐xSe (abbreviated as CSPQ) nanoparticles can ameliorate sevoflurane‐induced neurotoxicity by tuning the microglial lipid metabolism and promoting microglial M2‐like polarization via TREM2 signaling pathway, in which the apolipoprotein E (ApoE), and adenosine triphosphate‐binding cassette transporters (ABCA1 and ABCG1) levels are upregulated. Furthermore, the protective effects of CSPQ nanoparticles against sevoflurane‐induced neurotoxicity via TREM2 are further demonstrated by the small interfering RNA (siRNA)‐TREM2 transfected BV2 cells, which are obviously not influenced by CSPQ nanoparticles. The cell membrane coated CSPQ (referred as CSPQ@CM) nanoparticles can significantly reduce sevoflurane‐induced learning and memory deficits, improve lipid metabolism dysfunction, and promote the remyelination in the hippocampus of mice. The study shows great potential of targeting microglial lipid metabolism in promoting remyelination of neurons for treatment of neurotoxicity and neurodegenerative diseases.